Effect of Swimming as an Exercise on Peak Expiratory Flow Rate in Healthy Adult Females - Vishnu Ranade; Reena Sharma; Jaywant Nagulkar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction Swimming is a worldwide and popular sport and it is one of the known recreational activities across the world. Swimming helps to increase thoracic and abdominal muscle strength and thereby enhancing the ability to inflate the lungs. Regular swimming practice gives a positive effect on the lungs by increasing pulmonary capacity and thus improves the lung functions. The purpose of this study is to evaluate the effect swimming on PEFR in swimmers and non swimmers. Aim & Objectives To calculate the PEFR in swimmers & non swimmers adult females & to compare effect of swimming on PEFR. Materials and methodology Ethics approval & participant consent was taken.60 subject were included in the aged between 18-35.Out of them 30 were swimmers & 30 were non swimmers. Individual with cardiac and pulmonary disorder were excluded. Correct instructions were given to the patients according to the guidelines of national institute of Health. PEFR was taken in sitting position immidiately after swimming. Result Data collected was analyzed using proper statistical test which shows that, there was a significant difference in mean of PEFR in swimmers than non swimmers with p-value < 0.005. Conclusion The study concluded that there is a significant effect of swimming on peak expiratory flow rate in adult swimmer females. This study has demonstrated that exercise in the form of swimming produces a significant improvement in PEFR.